2014
DOI: 10.2105/ajph.2014.302150
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Sugar-Sweetened Beverage Consumption by Providing Caloric Information: How Black Adolescents Alter Their Purchases and Whether the Effects Persist

Abstract: Providing caloric information was associated with purchasing a smaller SSB, switching to a beverage with no calories, or opting to not purchase a beverage; there was a persistent effect on reducing SSB purchases after signs were removed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
97
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(99 citation statements)
references
References 39 publications
2
97
0
Order By: Relevance
“…About half of the 55 studies were randomized controlled trials 46,4955,5763,6571,7375,7780, 8385, 9698, 109110, 112118, 121124, 127129, 133 (29; 53%). The remaining studies utilized quasi-experimental designs, with either a two-group 64,76,86–90,104,106,111,119120,125,130132 (11; 20%), or one-group pretest-posttest 4748,56,72,8182,9195,99103,105,107108,126 (15; 27%) design.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…About half of the 55 studies were randomized controlled trials 46,4955,5763,6571,7375,7780, 8385, 9698, 109110, 112118, 121124, 127129, 133 (29; 53%). The remaining studies utilized quasi-experimental designs, with either a two-group 64,76,86–90,104,106,111,119120,125,130132 (11; 20%), or one-group pretest-posttest 4748,56,72,8182,9195,99103,105,107108,126 (15; 27%) design.…”
Section: Resultsmentioning
confidence: 99%
“…Nearly three-quarters of the interventions and policies (39; 71%) were implemented in schools or multiple settings including schools 46, 4955, 5764, 7072, 76, 80, 86–102, 104108, 110111, 114133 . Additional settings included home 6667,109,112113 (4; 7%), clinic 4748,56,65,6869,7375,7779 (7; 13%), and community-based organizations 8185,103 (5; 9%). Twenty of 55 (36%) studies identified SSB as their sole focus 56, 6264, 7072, 8485, 90, 96, 9899, 105106, 109, 112113, 120–125, 133 .…”
Section: Resultsmentioning
confidence: 99%
“…Different types of labels appear to give rise to different responses (86, 87). One small US study specific to SSBs suggests that providing prominent caloric information was associated with purchasing fewer SSB (88). There is evidence that front-of-pack symbols can have a positive impact on reformulation of foods (i.e.…”
Section: Policy Responsesmentioning
confidence: 99%
“…Future research could examine how to make calorie and nutrition information more salient; e.g. by listing the distance that must be walked to burn that number of calories for a person in energy balance (Bleich et al, 2014).…”
Section: Imperfect Informationmentioning
confidence: 99%